Clinical efficacy of GnRH analogue (busereIin) and oestradiol benzoate treatments in anoestrous buffaloes - Mohammed, Fateh; Dhaliwal, G S; Sharma, R K (The Indian Journal of Animal Sciences, 2012)
The clinical efficacy of GnRH analogue (buserelin) and oestradiol benzoate treatments in advancing the breeding seasons in anoestrous buffaloes was evaluated. Anoestrous buffaloes (31) were divided into 3 groups according to the treatment given to them. Buserelin (group 1, n = 10) and oestradiol (group 2, n = 13) were administered in lower (10 µg and 1 mg, respectively) or higher doses (20 µg and 2 mg, respectively) during the period extending from July to October, untreated anoestrous buffaloes (control 1, n = 8) and regularly cycling buffaloes (control 2, n = 9) were kept as controls. Buserelin included ovulatory heat within 20-32 days in 9 out of 13 treated buffaloes and 5 of them became pregnant. Oestradiol was able to induce ovulatory heat within 20-32 days in 9 out of 13 treated buffaloes, and 4 out of 7 buffaloes capable of conceiving became pregnant in this group. Buffaloes (2) in the control group expressed oestrous within 11.00±4.34 days and only 1 of them conceived. Higher doses of buscrelin (20 µg) and oestradiole (2 mg) were effective in inducing cyclicity. It was concluded that both buserelin and oestradiol benzoate, especially in higher doses (20 µg and 2 mg, respectively) were highly effective in including oestrus in anoestrous buffaloes during the transition period from low-to peak-breeding season.